2021
DOI: 10.1177/00207640211047882
|View full text |Cite
|
Sign up to set email alerts
|

‘Depression is not a familiar word’: A mixed-methods approach to describe the experience of primary care nurses treating depression in rural Guatemala

Abstract: Background: As the burden of mental health disorders continues to increase worldwide, there is significant need to describe the cultural variations in presentation, diagnosis and treatment of these diseases. An understanding of these variations can lead to the development of more effective programs to manage these conditions. In Guatemala, depression is the second-leading cause of disability and yet mental health treatment resources are scarce, particularly for indigenous individuals. Aims: The primary researc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 23 publications
(20 reference statements)
0
2
0
Order By: Relevance
“…Previous research in the community found that 21% of participating women had scores of ≥10 on the Patient Health Questionnaire–9 which, while not validated in Guatemala, is frequently used as a cutoff for screening major depression in international contexts, including Latin America, although cutoff scores may vary by context (Arrieta et al, 2017; Kroenke et al, 2010; Maupin & Hackman, 2022). Most participants did not report experiencing depression, however, and literature suggests the lack of knowledge regarding the signs and symptoms (Stryker et al, 2022). Yet, in the same study, 43.6% and 14.9% of women reported having nervios and susto in a 2-week illness recall task, respectively, indicating the cultural saliency and prevalence of CCDs.…”
Section: Mental Health In Guatemalamentioning
confidence: 99%
“…Previous research in the community found that 21% of participating women had scores of ≥10 on the Patient Health Questionnaire–9 which, while not validated in Guatemala, is frequently used as a cutoff for screening major depression in international contexts, including Latin America, although cutoff scores may vary by context (Arrieta et al, 2017; Kroenke et al, 2010; Maupin & Hackman, 2022). Most participants did not report experiencing depression, however, and literature suggests the lack of knowledge regarding the signs and symptoms (Stryker et al, 2022). Yet, in the same study, 43.6% and 14.9% of women reported having nervios and susto in a 2-week illness recall task, respectively, indicating the cultural saliency and prevalence of CCDs.…”
Section: Mental Health In Guatemalamentioning
confidence: 99%
“…Nurses from WK described high levels of depression in the communities in which they work, and significant barriers to specialized mental health services for their patients. They recognized a need for more community education about mental health, and an openness to receive more training themselves to be able to provide basic psychoeducation (Stryker et al, 2022). Therefore, a collaboration of partners from WK, UC, the Universidad de San Carlos de Guatemala (USAC) Quetzaltenango branch (whose medical students rotate with WK), and psychologists from the Universidad del Valle de Guatemala (UVG) and Proyecto Aiglé Guatemala piloted a virtual Project ECHO™ curriculum on mental health for primary care clinicians and students serving rural Guatemala.…”
Section: Context For the Current Studymentioning
confidence: 99%